Drug Abuse Warning Network (DAWN), 1997: (United States) ([Verlag nicht ermittelbar], 1999)
The Drug Abuse Warning Network (DAWN) survey is designed to capture data on emergency department (ED) episodes that are induced by or related to the use of an illicit, prescription, or over-the-counter drug. For purposes of this collection, a drug "episode" is an ED visit that was induced by or related to the use of an illegal drug or the nonmedical use of a legal drug for patients aged six years and older. A drug "mention" refers to a substance that was mentioned during a drug-related ED episode. Because up to four drugs can be reported for each drug abuse episode, there are more mentions than episodes in the data. Individual persons may also be included more than once in the data. Within each facility participating in DAWN, a designated reporter, usually a member of the emergency department or medical records staff, was responsible for identifying drug-related episodes and recording and submitting data on each case. An episode report was submitted for each patient visiting a DAWN emergency department whose presenting problem(s) was/were related to their own drug use. DAWN produces estimates of drug-related emergency department visits for 50 specific drugs, drug categories, or combinations of drugs, including the following: acetaminophen, alcohol in combination with other drugs, alprazolam, amitriptyline, amphetamines, aspirin, cocaine, codeine, diazepam, diphenhydramine, fluoxetine, heroin/morphine, inhalants/solvents/aerosols, LSD, lorazepam, marijuana/hashish, methadone, methamphetamine, and PCP/PCP in combination with other drugs. The use of alcohol alone is not reported. The route of administration and form of drug used (e.g., powder, tablet, liquid) are included for each drug. Data collected for DAWN also include drug use motive and total drug mentions in the episode, as well as race, age, patient disposition, reason for ED visit, and day of the week, quarter, and year of episode.